Kinerja keuangan berbasis Economic Value Added: Studi kasus pada PT Telkom Indonesia Tbk - Sukarno, Siti Rahma; Mintalangi, Syermi S. E. (Manajemen Bisnis dan Keuangan Korporat, 2024)
Measurement of financial performance is a systematic evaluation and analysis of a company's financial condition. Economic Value Added is a method to assess a company's financial performance by measuring the economic value created after accounting for the cost of capital. The purpose of this study is to determine the financial performance of PT Telkom Indonesia Tbk for 2020-2023 period using Economic Value Added Method. The research method used is descriptive qualitative. The result shows that the financial performance of PT Telkom Indonesia Tbk, based on the analysis of Economic Value Added (EVA) from 2020 to 2023 is considered good, where the value of EVA is EVA>0, or for four consecutive years the company EVA shows a positive result. This shows that PT Telkom Indonesia Tbk has succeeded in generating economic added value for the company from the capital invested by funders.